A Thousand Cuts: A Critical Analysis of the Retributive Response to Sexual and Intimate Partner Violence in Rural Ontario and a New Path Forward - Murdoch-Fyke, Airianna (Université d'Ottawa | University of Ottawa, 2026)
Sexual and intimate partner violence is the most underreported violent crime in Canada, particularly in rural Ontario, despite significant legal reforms intended to protect victims and encourage reporting. This thesis critically examines how the patriarchal foundations of the Canadian criminal justice system actively silences and deters women from reporting sexual and intimate partner violence and proposes that a restorative justice model, developed with a trauma informed and victim centric lens, should be offered as an alternative justice model to victims of sexual and intimate partner violence. This research specifically focuses on rural Ontario, where sexual and intimate partner violence rates are disproportionately high and access to support services is limited, and explores how personal, socio-cultural, and systemic, barriers compound to silence survivors. Drawing from feminist legal theory and restorative justice scholarship, this study argues that the adversarial nature of the criminal justice system is fundamentally incompatible with the individualized needs of victims and instead prioritizes the punishment of offenders over the healing of survivors. Through a comprehensive literature review and critical analysis, this research outlines a restorative justice model tailored to the rural Ontario context. This model emphasizes accountability, respect, and community engagement, aiming to reduce barriers to reporting while offering survivors agency, validation, and an opportunity to heal from the harm they experienced. Ultimately, this thesis advances the argument that only by shifting away from patriarchal legal structures and focusing on survivors’ voices can a truly just response to sexual and intimate partner violence be realized.
Keywords: intimate partner violence; restorative justice; sexual violence; rural Ontario; barriers to reporting; feminism